2005
DOI: 10.12930/0271-9517-25.2.20
|View full text |Cite
|
Sign up to set email alerts
|

Strengths-Based Advising: A New Lens for Higher Education

Abstract: Strengths-based advising is proposed as a new lens for higher education, one that enables advisors to see diverse groups of students fulfill their potential and achieve excellence. Based on research from social work, positive psychology, and the business world, this approach enables advisors to identify and build on the inherent talents students bring with them into the college and university setting, teaching students to develop and apply their strengths to new and challenging learning tasks. This explicit fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 31 publications
0
51
0
1
Order By: Relevance
“…It is also possible for students to create custom degree maps in which colleges offer structured degree programs that students can tailor to their educational goals with the help of an advisor (Bailey, Jaggars, & Jenkins, 2015). Advisors need to create intentional course scheduling opportunities that provide clear course pathways matched to students' motivation and goals (Muraskin & Lee, 2004;Schreiner & Anderson, 2005). Indeed, Bahr (2008) found that advising is positively related to student success and may be especially effective for low-performing students who may be navigating multiple levels of developmental math.…”
Section: Scaffolding In Course Sequencingmentioning
confidence: 99%
“…It is also possible for students to create custom degree maps in which colleges offer structured degree programs that students can tailor to their educational goals with the help of an advisor (Bailey, Jaggars, & Jenkins, 2015). Advisors need to create intentional course scheduling opportunities that provide clear course pathways matched to students' motivation and goals (Muraskin & Lee, 2004;Schreiner & Anderson, 2005). Indeed, Bahr (2008) found that advising is positively related to student success and may be especially effective for low-performing students who may be navigating multiple levels of developmental math.…”
Section: Scaffolding In Course Sequencingmentioning
confidence: 99%
“…[39][40][41][42][43][44][45][46][47][48][49][50] . Los estudiantes han mostrado gran interés por la PP, como se ilustra en el sorprendente incremento de la demanda por este tipo de cursos en pregrado y postgrado (Positive Psychology Faculty at Universities.…”
Section: Origen Y Principios Básicos De La Psicología Positivaunclassified
“…Staff go to great lengths to assess the abilities of entering college students and to place them in remedial courses or provide special services based on the deficits discovered in the assessment process (Schreiner & Anderson, 2005).…”
Section: The Role Of Assessmentmentioning
confidence: 99%
“…Addressing weaknesses can indeed result in at least short-term improvement: performance often improves, but not to levels of excellence and often at a very high price. Attrition rates remain very high among at-risk students, and low levels of academic motivation are often the norm (Schreiner & Anderson, 2005). In addition, as Yarbrough noted, advising encounters that consist of 'probing questions designed to illuminate and clarify the shortcomings and inadequacies of the student ...…”
Section: The Role Of Assessmentmentioning
confidence: 99%
See 1 more Smart Citation